2010
DOI: 10.1002/anie.201000655
|View full text |Cite
|
Sign up to set email alerts
|

Valeric Biofuels: A Platform of Cellulosic Transportation Fuels

Abstract: At the beginning of the 21st century mankind is facing an energy challenge as a consequence of the world s increasing energy demand, the depletion of "easy" oil and gas fields, and the impact of CO 2 emissions on the Earth s climate ("three hard truths"). [1] Much research is therefore being devoted to the exploration and development of new, carbon-lean energy sources. These include biofuels, which are the most promising option for the transportation sector in the coming decades. [2] The first generation of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
425
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 729 publications
(442 citation statements)
references
References 25 publications
12
425
0
5
Order By: Relevance
“…We must ensure that we hydrogenate only the keto group, enabling the cyclisation to the lactone product. Previous studies have shown that both the size and the dispersion of the ruthenium sites are crucial, as well as the properties of the support [17,21,32,33]. This is because the hydrogenation of keto group is catalysed by a combined effort of both the ruthenium active site and the support.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We must ensure that we hydrogenate only the keto group, enabling the cyclisation to the lactone product. Previous studies have shown that both the size and the dispersion of the ruthenium sites are crucial, as well as the properties of the support [17,21,32,33]. This is because the hydrogenation of keto group is catalysed by a combined effort of both the ruthenium active site and the support.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical, thermal and chemical properties of ZrO 2 are favourable for these reactions. It is stable under coking conditions and remains active even after a week's exposure to hot carboxylic acid [21]. Thus, we chose zirconia as support (ZrOH and ZrO 2 ) and prepared Ru/ZrO 2 catalysts using different pre-treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Duas publicações recentes por Bond et al 110 e Lange et al 111 sugerem que o ácido levulínico derivado por desidratação de glicose pode ser intermediário em processos de conversão catalítica para gerar ésteres do ácido valérico. 112 A transformação da γ-valerolactona na presença de Pb/Nb 2 O 6 gera como intermediários alquenos que sofrem posterior oligomerização para formar alcanos C 9 -C 16 com potencial de serem empregados como combustíveis líquidos tipo diesel.…”
Section: Figura 11 Representação Esquemática Simplificada Do Metabolunclassified
“…There has been significant recent interest in the use of valeric acid for the production of biodiesel [17 -21] and, in particular the use of the ketonic decarboxylation reaction to form 5-nonanone (see figure 1(b)) [22,23].…”
mentioning
confidence: 99%